Um olhar sobre a igreja Divino Espírito Santo do Cerrado - Natália Achcar Monteiro Silva (2014)
This study addresses the themes of collective memory and popular culture, contextualizing the work of Lina Bo Bardi (1914-1992) in Brazil. In particular, it emphasizes your project in the years 1976-1982, for the franciscan church of the Divino Espírito Santo do Cerrado, in Uberlândia/MG, analyzing the relationship between this architectural set and the community that uses it. Through interviews were recorded many memories of some members of the community group, as well as other agents who worked together somehow in place over time. During the process, with the contact with people and a collection of memories, it was still possible to build a new view of the researcher.